Translating Comic Strips as a Strategy to Enrich Students’ Vocabulary Mastery - Lilies Youlia Priatin; Leni Irianti; Zia Nurfauziah (International Journal of Innovation and Education Research, 2021)
This study aims to figure out the effectiveness in enriching students’ vocabulary mastery by implementing comic translation teaching technique. The method of the research is mixed method design with the type of true-experimental pre-test post-test control group design for the quantitative data and close-ended questionnaire for the qualitative data. The population of this study were the students of eight grade in one of the junior high schools in Tasikmalaya. the sample 30 students as the experimental group and 30 students as the control group. The two research instruments used were test and questionnaire. The vocabulary test in the form of finding the difficult word and making it a sentence was used to get the data of students’ level of vocabulary mastery, while questionnaire was used to know students’ perception toward the technique. Based on the data analysis, it is found that comic translation could improve students’ vocabulary mastery. This technique met the criteria of success since average of students’ score got 80 and students showed positive perception toward this technique.The preliminary study indicated that students’ problem in learning vocabulary was the limited vocabulary knowledge, thus, they performed low in language tasks. Comics were used as media in teaching vocabulary since it is an authentic material that contains rich vocabulary exposure for the students. It is suggested for the teacher to implement comic translation as an extensive vocabulary exposure activity during lesson.